EVALUATION OF ERYTHROCYTE SEDIMENTATION RATE (ESR) OF MOTORCYCLE WORKSHOP WORKER EXPOSED TO BENZENE - Moch. Sahri; Maharani Pertiwi Koentjoro; Shamsul Bahari Shamsudin (Universitas Nahdlatul Ulama Surabaya, 2019)
Occupational exposure to benzene from fuel oil in workshop motorcycle workshop causes several health effects, depending upon the level and duration of exposure. Analysis of blood is important to access the status of worker’ health. The study aimed to assess the gather basic information required for protecting workers’ health and improve working conditions in the works sites by investigating the ESR levels. A comparative cross-sectional study conducted in Surabaya City, East Java-Indonesia, which involved 100 workers. The occupational data collected using a structured questionnaire while blood analysis parameters measured with an automated hematology analyzer. The result showed that leukocytes, erythrocytes, hemoglobin (HGB), hematocrit values (HCT), platelet, MCV, RDW, eosinophil, basophils, neutrophil rods, neutrophil segment, lymphocyte, monocytes were in normal value. Whereas, MCH, MCHC, ESR has shown in abnormal value as average 24.5 pg, 29.18 g/dL and 8.21 mm/h, respectively. Those value, especially in ESR value indicated the increasing concentration plasma viscosity. This is may cause by inflammation in the workers’ body. To prevent the hazardous effect of benzene exposure, occupational health should be implemented for workers in order to protect them from exposure to benzene.